Pengaruh Kemampuan Berpikir Kritis Siswa Terhadap Hasil Belajar Pendidikan Agama Islam di SMA Negeri 1 Batipuh - Nurul Azzura; Sulaiman Sulaiman (FONDATIA, 2022)
This research is motivated by some students of SMA Negeri 1 Batipuh, that in terms of learning and learning outcomes, students are not entirely using critical thinking, because some children are not very successful in learning and learning outcomes, they just study according to their own needs. each other's abilities, especially if a subject has nothing to do with the child's ideals, so they are only limited in learning. Then this study aims to determine whether or not there is an influence of students' critical thinking skills on learning outcomes of Islamic Religious Education at SMA Negeri 1 Batipuh. This research uses associative quantitative research, with data analysis method using analysis prerequisite testing and hypothesis testing with T test. The population in this study is all students of class XI SMA Negeri 1 Batipuh. The sample in this study was 75 students consisting of each class from class xi totaling 9 classes. The results of the research obtained through a questionnaire for students' critical thinking skills on learning outcomes in the high category are evidenced by 48% of students in the high category. For learning outcomes of Islamic Religious Education in the high category as evidenced by 67% of students in the high category. And there is an influence between students' critical thinking skills on learning outcomes of Islamic Religious Education at SMA Negeri 1 Batipuh with an R square test of 0.399 (39.9%) which shows that the independent variable has an influence on the dependent variable.